Simulation-Based Digital Learning for Vocational Schools - Herdy Puradimaja; Aam Hamdani (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2022)
Students in vocational schools are generally faced with difficult material accompanied by learning facilities that are not optimal in attracting their attention. Simulation models can be done for students to practice appropriate skills in learning activities, the demands of the times in the era of the COVID-19 pandemic urge educators to produce digital simulation media that are suitable. Systematic Literature Review by analyzing documents and articles searched through an electronic database search engine use as method to be discussed. Simulation-based digital learning facilities require software in making simulation learning tools. Several simulators have been designed and applied to electrical learning in the automotive sector with the result that they can improve the quality of learning. Simulation-based digital technology provides practicality and completeness to user needs, especially those related to practical skills in vocational education. Meanwhile, there are still few simulators in the form of digital or software for learning electrical systems in the automotive sector.